Peran Lembaga Keuangan Syariah dalam Pemberdayaan UMKM di Indonesia - Singgih Muheramtohadi (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2017)
Syariah Financial Institution means that the financial institution is run based on the Islamic teaching that refers to Qur’an and the Sunnah. Practically, it beganin early history of Islam, then was developed into Syariah Financial Institution. So, the purpose of Syariah Financial Institution is not merely for profit orientation. Further, it should be in accordance with Islamic value and the human philanthropy. Most of Syariah Financial Institution’s financing is for business sector and its ability to reach the micro business, that can’t be done by commercial banks. The financing for small business is funded by Islamic institutions due to Grameen Bank effect. Previously, Grameen Bank was built in mid-decade of 1970. The Financing of Syariah Financial Institution, in any sort, including cooperative union or BMT (Baitul Maal wa Tamwil), increased over time in both Institution Revenue and the Financing Rate. According to Financial Service Authority, most of financing of Syariah Banking is for the Micro, Small, Medium Enterprises that is very important for the nation economy, because it is engaged in the real sector of economy. And the other characters of the Micro, Small, medium enterprises in Indonesia are holding the honesty ethics and resistante to the crisis. They are the strengths of UMKM which must be considered to make the decision by the government or the Financial Institutions.Lembaga Keuangan Syariah (LKS) berarti badan yang bergerak di bidang keuangan yang dilandaskan pada ajaran Islam yang bersumber pada al Qur’an dan As Sunnah. Praktek ini sudah terdapat pada sejarah awal Islam, dan asas moralitas Islam dikembangkan dalam bentuk LKS. Sehingga, tujuan dari LKS tidak semata Profit Oriented, melainkan terdapat unsur-unsur keislaman dan kemanusiaan di dalamnya. Lembaga Keuangan syariah sebagian besar pembiayaannya diperuntukkan kepada sektor usaha, dan punya kemampuan untuk menjangkau usaha mikro, Sesuatu yang jarang dilakukan oleh pihak perbankan konvensional. Pembiayaan kepada UMKM ini tidak lepas juga dari pengaruh Grameen Bank sebelumnya, yang telah berdiri sejak medio 1970-an. Pembiayaan Lembaga Keuangan Syarah, baik dalam wujud Bank, Koperasi Simpan Pinjam maupun BMT mengalami peningkatan dari waktu ke waktu. Baik itu dari segi omzet LKS maupun tingkat pembiayaan nya. Berdasarkan data dari Jasa Otoritas Keuangan sebagian besar dari pembiayaan tersebut disalurkan kepada UMKM. Pembiayaan UMKM sangat penting dalam perekonomian nasional, karena bergerak di sektor riil. Karakteristik UMKM adalah sebagai usaha menengah ke bawah, pada umumnya dikelola dengan etika kejujuran masih dipegang kuat, serta relatif lebih kuat ketika dihadapkan pada krisis. Inilah yang jadi potensi UMKM yang harus diperhatikan dalam mengambil keputusan publik, baik itu oleh Pemerintah maupun Lembaga Keuangan (perbankan).